Extractive Spectrophotometric Method for the Determination of Some Antipsychotic Drugs Using Eriochrome Black T - Akram M. El-Didamony, Sameh M. Hafeez, Ismail I. Ali (Journal of Applied Pharmaceutical Science, 2015)
Simple, accurate, precise, and rapid extractive spectrophotometric method was developed for the determination of four antipsychotics drugs, namely sulpiride (SUP), olanzapine (OLP), clozapine (CLP) and aripiprazole (ARP) both in tablets and in biological fluids. The method was based on the formation of red colored ion-pair complex between the studied drugs and eriochrome black T (EBT) with absorption maxima at 514 nm. The stoichiometry of the complexes in either case was found to be 1: 1 and the conditional stability constant (Kf) of the complexes have been calculated. Reaction conditions were optimized to obtain the maximum color intensity. Beer’s law was obeyed in the concentration ranges of 4-30, 4-20, 2-18 and 4-26 µg/ml with SUP, OLP, CLP and ARP, respectively. Various analytical parameters have been evaluated and the results have been validated by satistical data. The proposed method was successfully applied to the analysis of commercial tablets containing the drugs and the results were in good agreement with those obtained with reported methods. The proposed method was further applied to the determination of the studied drugs in spiked human serum and urine. A proposal for the reaction pathway was postulated.
Keywords: Sulpiride, Olanzapine, Clozapine, Aripiprazole, Ion-pair complex, Eriochrome black T.